2017
DOI: 10.1021/acs.nanolett.7b01523
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular Recording of Spontaneous Action Potentials in Mammalian Neurons and Cardiac Cells with 3D Plasmonic Nanoelectrodes

Abstract: Three-dimensional vertical micro- and nanostructures can enhance the signal quality of multielectrode arrays and promise to become the prime methodology for the investigation of large networks of electrogenic cells. So far, access to the intracellular environment has been obtained via spontaneous poration, electroporation, or by surface functionalization of the micro/nanostructures; however, these methods still suffer from some limitations due to their intrinsic characteristics that limit their widespread use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
242
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(247 citation statements)
references
References 26 publications
(63 reference statements)
4
242
0
1
Order By: Relevance
“…However, penetration can be enhanced via electroporation (Figure G), optoporation (Figure H), or by coating nanostraws with strongly cell‐adhering coatings . Bioelectronic experiments show that nanoelectrodes only measure intracellular potentials after poration techniques have been applied, and rapidly return to measuring extracellular potentials in the absence of further external stimulus, again highlighting the need for an external force to disrupt the membrane. Dipalo et al explored this behavior explicitly using a range of nanopillar geometries using fluorescent and electron microscopy, and electrophysiological measurements .…”
Section: Understanding the Cell–nanostructure Interfacementioning
confidence: 99%
See 3 more Smart Citations
“…However, penetration can be enhanced via electroporation (Figure G), optoporation (Figure H), or by coating nanostraws with strongly cell‐adhering coatings . Bioelectronic experiments show that nanoelectrodes only measure intracellular potentials after poration techniques have been applied, and rapidly return to measuring extracellular potentials in the absence of further external stimulus, again highlighting the need for an external force to disrupt the membrane. Dipalo et al explored this behavior explicitly using a range of nanopillar geometries using fluorescent and electron microscopy, and electrophysiological measurements .…”
Section: Understanding the Cell–nanostructure Interfacementioning
confidence: 99%
“…The use of electroporation to facilitate intracellular electrical access is common throughout the literature and is consistent with the use of electroporation to enhance intracellular delivery, as discussed above. Some have argued that this is problematic when studying neuronal networks, as electroporation overly perturbs the electroanatomy of the cells under investigation and can cause damage to the nuclear membrane . Indeed, Hai and Spira have proposed that electroporation on nanostructures can itself be a technique to study membrane repair dynamics …”
Section: Bioelectronic Stimulation and Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to this, M. Dipalo et al 53 has recently shown that optical methods can be used to aid device integration. Highlighting a previously described method for generating transient holes in the cell membrane via a plasmonicly created pressure waves 54 , they were able to optically introduce nanocylinder electrodes intracellularly in a non-invasive manner.…”
Section: Plasmonics Enabled Optoporation For Intracellular Neural Recmentioning
confidence: 99%